Measurements of Location-Dependent Nitric Oxide Levels on Skin Surface in relation to Acupuncture Point. (24th September 2012) - Ha, Yejin; Kim, Misun; Nah, Jiseon; Suh, Minah; Lee, Youngmi
Abstract : Location-dependent skin surface's partial nitric oxide pressure (pNO) is studied using highly sensitive amperometric NO microsensor with a small sensing area (diameter  = 76  μ m). The pNO level of LI4 (Hegu) acupuncture point is measured and compared with the pNO level of nonacupuncture point. In addition, the mapping of pNO is carried out over the left wrist skin area one- as well as two-dimensionally. Statistically higher pNO levels near the position of acupuncture points than non-acupuncture points are observed consistently, implying tight relationship between the level of NO release of skin and acupuncture points. The amperometric planar NO microsensor successfully monitors the heterogeneity of skin pNO distribution in high spatial resolution due to its advantageous features such as high sensitivity and small sensing dimension. The current study suggests the direct connection between NO and acupuncture points and possibly provides beneficial information to understand physiological roles and basis of the acupuncture points.